2010
DOI: 10.4103/1596-3519.62618
|View full text |Cite
|
Sign up to set email alerts
|

Do women want disclosure of fetal gender during prenatal ultrasound scan?

Abstract: Most of the pregnant women (94%) would want disclosure of fetal gender at prenatal ultrasound scan. Only 5.5% of the women would not want fetal sex disclosure because they were satisfied with whichever that was there. It is advisable for the sonologist to be discrete on what to say during the procedure especially as it relates to fetal sex so as not to hurt those that do not want disclosure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
2
10
1
Order By: Relevance
“…[ 19 ] This shows that there is still much emphasis placed on the sex of the child in our environment. However, this contrasts with a report from Sokoto in Northern Nigeria[ 21 ] where women were indifferent about gender of their babies, preferring to be “satisfied with anyone that comes”. The desire to know the gender of the fetus before delivery has been cited as one of the drawbacks of ultrasound as this has resulted in sex selective abortions especially in a society with strong male preference.…”
Section: Discussioncontrasting
confidence: 72%
“…[ 19 ] This shows that there is still much emphasis placed on the sex of the child in our environment. However, this contrasts with a report from Sokoto in Northern Nigeria[ 21 ] where women were indifferent about gender of their babies, preferring to be “satisfied with anyone that comes”. The desire to know the gender of the fetus before delivery has been cited as one of the drawbacks of ultrasound as this has resulted in sex selective abortions especially in a society with strong male preference.…”
Section: Discussioncontrasting
confidence: 72%
“…[13] Majority of our respondents desired disclosure of fetal gender to them, which is in agreement with reports of previous studies. [111314] Furthermore, a study in Uganda reported that Ugandan parturients have a strong desire to know fetal sex at ultrasound. [6] Other studies, in contrast, have also reported that only a small proportion of obstetric patients seeks to know fetal gender.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that a majority of Nigerian parturients desire to know the gender of their fetus during prenatal ultrasound scan. [11121314] Furthermore, in Uganda, parturients expressed a strong desire to know fetal sex at ultrasound. [6] The desire to know fetal gender may be attributed to societal pressure as a previous study reported that 50% of undergraduate students prefer their first child to be male.…”
Section: Introductionmentioning
confidence: 99%
“… 1 This practice is tolerated because there is no evidence or scientifically proven harm to the fetus. 1 , 2 Gender identification can be done by ultrasonography more reliably from 16 weeks of pregnancy, 1 3 and by the 20th week of gestation, the accuracy is close to 97%. 2 …”
Section: Introductionmentioning
confidence: 95%
“…Previous studies in Nigeria have shown that the majority number of women desire to know the gender of their fetus during prenatal ultrasound scan. 2 , 9 , 10 , 17 This desire is equally expressed by women in Uganda, 6 People’s Republic of China, 18 , 19 Pakistan, 20 and Nepal. 21 …”
Section: Introductionmentioning
confidence: 99%